Aprendendo por meio de experiências com situações problema - Belo, Rosangela dos Santos [UNESP] (2016)
With the objective expand the experiences with the update of Methodology of Resolution of Problems, angled for best the practical of teacher and the motivation of the use this strategy methodological in their dynamics of class, propose the discussion of how the instructors can learn through of use of problem situation, in order to promote the overcoming of their difficulties and mistakes, contribute to the perfecting of their arguments and in validation of their answers. In development this project approach some aspects that think relevant to geometry teaching, more specific of calculations of perimeters and area plane figures. To report experiences collected the work performed with first year of high school students in Profª Maria Evanilda Gomes school, located in Itororó do Paranapanema, district of Pirapozinho city, accompanied from august of 2014. To promote a vision general of school performance this class, search collect the informations submitted by Secretaria da Educação do Estado de São Paulo, in Relatório Pedagógico about the SARESP (Sistema de Avaliação de Rendimento Escolar do Estado de São Paulo) 2013, IDESP (Índice de Desenvolvimento da Educação do Estado de São Paulo) 2013 and results obtained in diagnostics tests referents the class in question. Therefore utilized important indicators that depict the reality of the school and that formed the basis for the development of this Project.